Global metabolic inhibitors of sialyl- and fucosyltransferases remodel the glycome - Rillahan, Cory D; Antonopoulos, Aristotelis; Lefort, Craig T; Sonon, Roberto; Azadi, Parastoo; Ley, Klaus; Dell, Anne; Haslam, Stuart M; Paulson, James C (Nature chemical biology, 2012)
Fluorinated, cell-permeable analogs of sialic acid and fucose are processed by monosaccharide salvage pathways to generate sialyl- and fucosyltransferase inhibitors intracellularly. These compounds serve as important new tools to dissect the role of glycan modifications within complex biological systems. Despite the fundamental roles of sialyl- and fucosyltransferases in mammalian physiology, there are few pharmacological tools to manipulate their function in a cellular setting. Although fluorinated analogs of the donor substrates are well-established transition state inhibitors of these enzymes, they are not membrane permeable. By exploiting promiscuous monosaccharide salvage pathways, we show that fluorinated analogs of sialic acid and fucose can be taken up and metabolized to the desired donor substrate–based inhibitors inside the cell. Because of the existence of metabolic feedback loops, they also act to prevent the de novo synthesis of the natural substrates, resulting in a global, family-wide shutdown of sialyl- and/or fucosyltransferases and remodeling of cell-surface glycans. As an example of the functional consequences, the inhibitors substantially reduce expression of the sialylated and fucosylated ligand sialyl Lewis X on myeloid cells, resulting in loss of selectin binding and impaired leukocyte rolling.